DIGITAL TRANSFORMATION AND CUSTOMER SATISFACTION IN INDONESIAN BANKING SECTOR - Arif Budi Raharja; Muhamad Abi Dunya; Zaenal Aripin (PT. Kreatif Indonesia Satu, 2024)
Background: Indonesian banking sector undergoes rapid digital transformation driven by technological advancement and changing customer expectations. Aims: This study examines relationships between digital transformation initiatives and customer satisfaction in Indonesian banks. Research Method: Survey-based quantitative approach involving 312 banking customers across major Indonesian cities, supplemented by interviews with 15 bank executives. Results and Conclusion: Digital transformation significantly enhances customer satisfaction through improved service accessibility, transaction efficiency, and personalized experiences. Mobile banking adoption reached 87 percent among surveyed customers, with 73 percent reporting increased satisfaction. However, digital divide issues affect older customers and rural populations. Contribution: Research provides insights for Indonesian banks to optimize digital transformation strategies while maintaining inclusive service delivery across diverse customer segments.